A legal study on the right to education of stateless children in Malaysia / Karl Rafiq Nadzarin…[et al.] - Nadzarin, Karl Rafiq; Rahmat, Muhammad Fuzail; Abu Bakar, Nadia; Alexius Kiob, Adam (2010)
This paper is a study done on stateless children and their right to education in Malaysia. Statelessness is a very serious issue in the world today and many governments around the world are learning to deal with this issue. The United Nations various bodies, particularly the United Nations High Commissioner for Refugees have been assisting states around the world on this matter and have been extensively campaigning for general awareness on the issue and problems associated with statelessness. According to the Universal Declaration of Human Rights, every child and person deserves the right to a free education. However, many circumstances prevent this from happening. In Malaysia, this is a problem attributed to many minority communities such as the refugees, asylum seekers and the stateless as the state does not legally recognize the existence of any of these communities. Therefore, they cannot enter local public schools and their rights are not protected. How then is this issue dealt with locally? Or is it ignored completely? Does the state have a legal obligation towards these stateless children with respect to the right to education? This paper will attempt to answer these questions and explore the socio-legal aspects on the subject matter which shall include an analysis of the local and international law, policies and compare it with realities on the ground. Recommendations and suggestions will also be provided to solve this issue with the basic premise of awarding benefit to every party once the right to education is awarded to stateless children in Malaysia.